Editorial board, information for authors, and other front matter - Lisa Lundy (Journal of Applied Communications, 2011)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 95, no. 1 (2011) of Journal of Applied Communications
Keywords: masthead